2003
DOI: 10.1161/01.hyp.0000049163.23426.66
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase Attenuates Angiotensin II-Mediated Increase in Cyclooxygenase-2 Activity in Human Femoral Endothelial Cells

Abstract: Abstract-Heme oxygenase (HO) regulates cellular heme levels and catalyzes the formation of bilirubin and carbon monoxide. We hypothesize that the status of the endothelial HO system influences the angiotensin (Ang) II-induced increase in the endothelial production of prostaglandin I 2 (PGI 2 ) (measured as 6-keto-PGF 1␣ ) and prostaglandin E 2 (PGE 2 ), eicosanoids that modulate the vascular actions of Ang II. In the present study, we determined the effect of interventions that suppress HO activity or induce H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…Indeed, Ejima and Perrella (27) demonstrated that in the absence of COX-2 there is no up-regulation of HO-1 following LPS treatment in mice, demonstrating that COX is actually the stimulus for HO-1 expression. In contrast, but in agreement with these data, prior induction of HO-1 by gene therapy or by chemical products, such as cobalt protoporphyrin, abrogates COX-2 expression in various inflammatory models (28)(29)(30). Similarly, treatment with a COX-2 inhibitor is associated with HO-1 up-regulation (31).…”
Section: Discussionsupporting
confidence: 70%
“…Indeed, Ejima and Perrella (27) demonstrated that in the absence of COX-2 there is no up-regulation of HO-1 following LPS treatment in mice, demonstrating that COX is actually the stimulus for HO-1 expression. In contrast, but in agreement with these data, prior induction of HO-1 by gene therapy or by chemical products, such as cobalt protoporphyrin, abrogates COX-2 expression in various inflammatory models (28)(29)(30). Similarly, treatment with a COX-2 inhibitor is associated with HO-1 up-regulation (31).…”
Section: Discussionsupporting
confidence: 70%
“…Upregulation of HO-1 inhibits the inflammatory response, presumably by a decrease in cellular heme-mediated oxidative stress (50) and vasoconstrictors (46,(51)(52)(53)(54)(55). Consistent with these observations, mice and humans who are deficient in HO-1 experience progressive chronic inflammation and are sensitive to stressful injury, presumably as a result of elevated cellular heme and iron (56,57).…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, recent publications have shown a direct association between COX-2 and FGF-2 (Baguma-Nibasheka et al, 2007), and COX-2 mRNA has been shown to increase in response to FGF-2 administration in retinal epithelial cells, (Ershov and Basan, 1999). A decrease in COX-2 and an increase in HO-1 activity have also been observed in endothelial cells (Morimoto et al, 2001;Li et al, 2003), suggesting that the heme-hemoxygenase system could be a negative regulator for COX-2 expression. In summary, it is obvious that this study has some limitations due to two facts, namely that it is an in vivo study and, as such, it is hard to isolate one single effect, and that most of the experiments are not quantitative, so they only refl ect a relationship between the compared proteins.…”
Section: Discussionmentioning
confidence: 87%